INTEGRASI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK), PADA TAHAP PENYIDIKAN DALAM MEMENUHI HAK KORBAN TINDAK PIDANA KEKERASAN SEKSUAL - Muh Sutri Mamsyah; La Ode Bunga Ali (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2024)
Fulfilling the rights of victims of criminal sexual violence is very important, starting from procedural rights, medical rights, psychological rights, and physical protection, but it is often forgotten by law enforcement officials. This research will analyze the Witness and Victim Protection Agency (LPSK) integration model at the investigation stage in fulfilling the rights of victims of criminal sexual violence. This research uses normative juridical, legislative research approaches, primary legal materials on the Witness and Victim Protection Law, the Sexual Violence Crime Law. Secondary legal materials, journals, books and other references that have relevance to this research. The analysis technique used is descriptive analytical, the interpretation used is systematic and grammatical. The results of the research state that the LPSK integration model at the investigation stage has been regulated in Article 43 of the Sexual Violence Law, within 1 x 24 (one time twenty four) hours from the granting of temporary protection, the investigator is obliged to submit a request for protection to the LPSK. However, problems arise if the investigator does not apply for protection or ignores these legal obligations. This creates a legal vacuum. Future suggestions for the government and law enforcement agencies need to align perceptions regarding the protection of victims of sexual violence and the involvement of LPSK in the criminal justice system. In this way, it is hoped that the rights of victims can be fulfilled.